Antibacterial Effect of Iron Nanoparticles (FeNPs) on Acinetobacter baumannii - Mennat Allah Jamal Ahmed; Suha Maher Abed; Arshad Mahdi Hamad (Medical Journal of Babylon)
Background: Excessive and incorrect use of antibiotics has led to the emergence of strains of Acinetobacter baumannii that have resistance to antibiotics, multidrug resistance A. aumannii has become a real threat to life of humans. So scientists have resorted to using nanotechnology to limit the spread of infection with these strains. Objectives: This study aimed to use an eco-friendly method for synthesizing iron nanoparticles FeNPs using Cinnamon extract as a reducing and stabilizing agent. Also, explore the antibacterial activity of FeNPs against A. baumannii. Materials and Methods: The Iron nanoparticles (FeNPs) are synthesized by what is called (green synthesis) the easiest and nontoxic method, as microorganisms or plant extracts are used. We discuss how to synthesize FeNPs using plant extracts, where cinnamon powder was used and prepared as a plant extract to obtain FeNPs by adding 5 mL of the extract to 100 mL of aqueous iron nitrate and conducting tests for these nanoparticles, which include (UV, SEM, XRD, and FTIR). As well as studying the effect of iron nanoparticles as an antibiotic on many strains of A. baumannii with multidrug resistance using different concentrations as follows (0.1 M, 0.01 M, 0.001 M, and 0.0001 M). Results: This study showed that UV recorded approximately 360 nm, and SEM images exhibited spherical shape FeNPs nanostructures with an average size of 12.44 nm. The maximum inhibition diameter FeNPs against A. baumannii isolates was recorded at 33 mm in diameter. Conclusion: The preparation of FeNPs with cinnamon extract is a quick, nontoxic giving significant antibacterial effect on A. baumannii isolates.